Estructura poblacional y parámetros demográficos de Juniperus flaccida Schltdl. - Ayerde-Lozada, Demetrio; López-Mata, Lauro (Instituto de Ecología, A.C., 2016)
The purpose of this work was to compare the population structure and some demographic parameters of Juniperus flaccida between two populations in order to contribute for a better understanding of the management practices, as well as the use and conservation of this species. Two permanent plots of1ha each one were settled down under different perturbation conditions to compare both, the population structures and demographic parameters of Juniperus flaccida. Perturbation conditions were: for plot P1, with selective wood extraction and presence of cattle grazing, and for plot P2 with neither selective wood extraction nor cattle grazing but natural disturbances. In each plot all individuals of J. flaccida were marked, numbered and measured in their height, diameter to breast height (dbh) and survival, growth and fecundity were estimated on an annual basis in both plots. Population density and sex ratio (males:females) were estimated for each plot, and based on height and dbh individual parameters each population was structured in 8 size categories. The densities of the categories of both population sizes showed differences statistically significant between them. The sex ratio did not present significant differences from a theoretical 1:1 ratio in the population with selective wood extraction and cattle grazing. On the other hand, there were significant differences in the population without wood extraction. The frequencies of mortality by size categories showed significant differences into populations. The absolute rate growth of mature individuals and their fecundities were higher in the plot with wood extraction and cattle grazing. The differences in both population structures and demographic parameters of the population were associated with the perturbation conditions.